2018
DOI: 10.3389/fphys.2018.00546
|View full text |Cite
|
Sign up to set email alerts
|

Sinoatrial Beat to Beat Variability Assessed by Contraction Strength in Addition to the Interbeat Interval

Abstract: Beat to beat variability of cardiac tissue or isolated cells is frequently investigated by determining time intervals from electrode measurements in order to compute scale dependent or scale independent parameters. In this study, we utilize high-speed video camera recordings to investigate the variability of intervals as well as mechanical contraction strengths and relative contraction strengths with nonlinear analyses. Additionally, the video setup allowed us simultaneous electrode registrations of extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…5) may be explained by the decreased acetylcholine (ACh) release in HF. In an animal study Ahammer et al reported that decreased ACh increased beat-to-beat contraction strength variability of murine atrial preparation [51]. In that study hearts were removed, and the atria were dissected from the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…5) may be explained by the decreased acetylcholine (ACh) release in HF. In an animal study Ahammer et al reported that decreased ACh increased beat-to-beat contraction strength variability of murine atrial preparation [51]. In that study hearts were removed, and the atria were dissected from the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…Intact SAN/atrial tissue was isolated from the excised mouse heart in Tyrode’s solution prewarmed to 37 °C as described previously ( 17 , 40 ). The right and the left atria were pinned flat to the bottom of a 35-mm cell culture dish coated with Sylgard (Sylgard 184 Silicone elastomer kit; Dow Corning) of ~2-mm thickness.…”
Section: Methodsmentioning
confidence: 99%